Elementary Statistics: A Step by Step Approach - Bluman Allan G (McGraw-Hill, 2006)
ELEMENTARY STATISTICS: A STEP BY STEP APPROACH is for general beginning statistics courses with a basic algebra prerequisite. The book is non-theoretical, explaining concepts intuitively and teaching problem solving through worked examples and step-by-step instructions. This edition features increased emphasis on Excel, MINITAB, and the TI-83 Plus graphing calculator, computing technologies commonly used in such courses.